Nurses’ professional values and organizational commitment - Roaa Gassas, PhD; Olfat Salem, Rn PhD (Journal of Taibah University Medical Sciences, 2023)
الملخص: الأهداف البحثية: تتأثر القيم المهنية والإلتزام التنظيمي بشدة بالإختلافات الفردية. إن معرفة ماهية وكيفية عمل هذه الإختلافات هو أمر بالغ الأهمية لكل منظمة صحية. لذلك فإن الهدف من هذه الدراسة هو دراسة كيفية انعكاس الإختلافات في الخصائص الديموغرافية في القيم المهنية والإلتزام التنظيمي بين الممرضين والممرضات. طرق البحث: أجريت الدراسة باستخدام تصميم ارتباط وصفي مقطعي. تم استخدام القيم المهنية التمريضية ومقاييس الإلتزام التنظيمي لجمع البيانات. تكونت العينة من 412 ممرضً وممرضة ممن رغبوا في الإلتحاق بالدراسة. نتائج البحث: أظهرت النتائج أن القيم المهنية للممرضين والممرضات تختلف باختلاف العوامل الديموغرافية مثل الخبرة والقسم وأسباب اختيار المهنة وأخذ دورة أخلاقية، بينما لا توجد فروق على أساس التعليم أو الجنس. تختلف مستويات الإلتزام بإختلاف الخبرات والدين بالإضافة لحصولهم على دورة في علم الأخلاق وآداب المهنة. خلاصة البحث: يمكن أن تساهم المعرفة حول ما يمكن أن يؤثر على قيم وإلتزام الممرضين والممرضات في إعادة تصميم تعليم الأخلاقيات السريرية وتطوير خطط الإستقطاب الوظيفي. Abstract: Objectives: Both professional values and organizational commitment are strongly affected by variations among individuals. Identifying personal differences and their effects on professional values and organizational commitment is crucial for every hospital setting. Therefore, the aim of this study was to examine how differences in demographic characteristics are reflected in professional values and organizational commitment among nurses. Methods: The study used a cross-sectional descriptive correlational design. Nursing professional values and organizational commitment scales were used to collect the data. The sample consisted of 412 staff nurses recruited through a convenience sampling technique. Results: Nurses' professional values differed according to demographic factors such as experience, department, career choice and having taken an ethics course, whereas no differences associated with education or gender were observed. Nurses’ levels of commitment differed according to their experience, their religion and whether they had taken an ethics course. Conclusion: Deeper knowledge regarding the factors affecting nurses’ values and commitment may contribute to redesigning clinical ethics education for nurses and the development of non-traditional retention plans.